Multiple aspects of amyloid dynamics in vivo integrate to establish prion variant dominance in yeast - Norton, Jennifer; Seah, Nicole; Santiago, Fabian; Sindi, Suzanne S.; Serio, Tricia R. (Frontiers in Molecular Neuroscience, 2024)
Prion variants are self-perpetuating conformers of a single protein that assemble into amyloid fibers and confer unique phenotypic states. Multiple prion variants can arise, particularly in response to changing environments, and interact within an organism. These interactions are often competitive, with one variant establishing phenotypic dominance over the others. This dominance has been linked to the competition for non-prion state protein, which must be converted to the prion state via a nucleated polymerization mechanism. However, the intrinsic rates of conversion, determined by the conformation of the variant, cannot explain prion variant dominance, suggesting a more complex interaction. Using the yeast prion system [PSI+], we have determined the mechanism of dominance of the [PSI+]Strong variant over the [PSI+]Weak variant in vivo. When mixed by mating, phenotypic dominance is established in zygotes, but the two variants persist and co-exist in the lineage descended from this cell. [PSI+]Strong propagons, the heritable unit, are amplified at the expense of [PSI+]Weak propagons, through the efficient conversion of soluble Sup35 protein, as revealed by fluorescence photobleaching experiments employing variant-specific mutants of Sup35. This competition, however, is highly sensitive to the fragmentation of [PSI+]Strong amyloid fibers, with even transient inhibition of the fragmentation catalyst Hsp104 promoting amplification of [PSI+]Weak propagons. Reducing the number of [PSI+]Strong propagons prior to mating, similarly promotes [PSI+]Weak amplification and conversion of soluble Sup35, indicating that template number and conversion efficiency combine to determine dominance. Thus, prion variant dominance is not an absolute hierarchy but rather an outcome arising from the dynamic interplay between unique protein conformations and their interactions with distinct cellular proteostatic niches.